Zirconium Alloys for Orthopaedic and Dental Applications. Issue 9 (22nd June 2018) - Mehjabeen, Afrin; Song, Tingting; Xu, Wei; Tang, Hui Ping; Qian, Ma
Abstract : Zirconium alloys for biomedical applications are receiving increasing attention due to their two unique properties: 1) the formation of an intrinsic bone‐like apatite layer on their surfaces in body environments, and 2) better compatibility with magnetic resonance imaging (MRI) diagnostics due to their low magnetic susceptibility, as well as their overall excellent biocompatibility, mechanical properties, and bio‐corrosion resistance. In particular, since both of the MRI quality and speed depend on magnetic field strength, there is a compelling drive for use of high magnetic field strength (>3 Tesla) MRI systems. This paper provides a comprehensive review of the characteristics of commercially pure (CP) Zr and Zr‐based alloys as orthopaedic and dental implant materials. These include their 1) phase transformations; 2) unique properties including corrosion resistance, biocompatibility, magnetic susceptibility, shape memory effect, and super‐elasticity; 3) mechanical properties; 4) current orthopaedic and dental applications; and 5) the d‐ electron theory for Zr alloy design and novel Zr‐alloys. The mechanical properties of Zr‐based bulk metallic glasses (BMGs) and their application as implant materials are also assessed. Future directions for extending the use of Zr‐alloys as orthopaedic and dental implants are discussed. Abstract : Zirconium‐based alloys are receiving increasing attention as implant candidate materials due to their superior biocompatibility, good mechanical properties, and low magnetic susceptibility. This paper reviews the unique properties of recently developed zirconium‐based alloys and future directions for their design.